Theory of metasurface based perfect absorbers. (17th November 2017) - Alaee, Rasoul; Albooyeh, Mohammad; Rockstuhl, Carsten
Abstract: Based on an analytic approach, we present a theoretical review on the absorption, scattering, and extinction of both dipole scatterers and regular arrays composed of such scatterers i.e. metasurfaces. Besides offering a tutorial by outlining the maximum absorption limit for electrically/magnetically resonant dipole particles/metasurfaces, we give an educative analytical approach to their analysis. Moreover, we put forward the analysis of two known alternatives in providing perfect absorbers out of electrically and or magnetically resonant metasurfaces; one is based on the simultaneous presence of both electric and magnetic responses in so called Huygens metasurfaces while the other is established upon the presence of a back reflector in so called Salisbury absorbers. Our work is supported by several numerical examples to clarify the discussions in each stage.